2023
DOI: 10.3390/insects14090746
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Insecticides against the Invasive Apricot Aphid, Myzus mumecola

Dania H. Tabet,
Edoardo Visentin,
Martina Bonadio
et al.

Abstract: The invasive apricot aphid (Myzus mumecola Matsumura) is an important pest of apricot trees (Prunus armeniaca L.). In the presented study, laboratory bioassays using treated leaf disks of apricot were conducted to test the efficacy of twelve insecticides according to the maximum field dose. Additionally, dose-response curves were established for selected insecticides, and the effects on colony development were evaluated. Furthermore, a field trial was conducted to investigate the effectiveness of commonly used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In organic farming, this includes applications of mineral and plant oils, neem, pyrethrins or soaps (Penvern et al., 2010). A screening showed that insecticides allowed for organic production have a minor efficiency in the successful control of M. mumecola compared to those used in integrated pest management (Tabet et al., 2023). Therefore, especially in organic farming, where fewer control options are available, the production of large colonies caused considerable damage.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In organic farming, this includes applications of mineral and plant oils, neem, pyrethrins or soaps (Penvern et al., 2010). A screening showed that insecticides allowed for organic production have a minor efficiency in the successful control of M. mumecola compared to those used in integrated pest management (Tabet et al., 2023). Therefore, especially in organic farming, where fewer control options are available, the production of large colonies caused considerable damage.…”
Section: Resultsmentioning
confidence: 99%
“…Sampled aphids were identified based on their morphological characteristics using stereo-and light microscopy. Other aphid species found in the past on apricot trees in Europe differ significantly in terms of size and colour (Blackman & Eastop, 1994;Borbély et al, 2021;Panini et al, 2017;Petrović-Obradović, 2021;Tabet et al, 2023).…”
Section: Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Arthropod pests are among the major unintentionally introduced species and their invasion trend is projected to increase over time, especially in Europe, where they cause significant economic losses and ecological disruptions [5]. Although current guidelines promote integrated pest management (IPM) programs that minimize chemical inputs, insecticides represent the main tool approached by farmers to manage invasive pest infestations [6][7][8]. This attitude is largely due to the lack of cost-effective control strategies in the invaded regions [9][10][11] and the effectiveness of chemical insecticides for a quick reduction in pest populations [12,13].…”
Section: Introductionmentioning
confidence: 99%